EVALUASI PROGRAM MENTORING KEISLAMAN DI SDIT AL QALAM KOTA MAKASSAR - Muthmainnah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2023)
This research describes the Islamic Religious Assistance Program at SDIT Al Qalam Makassar using the CIPP evaluation model. This type of research is a program evaluation using the CIPP evaluation model with a qualitative approach. The data sources for this research are mentoring program implementers and mentoring implementation documents. The data collection methods used were observation, interviews, and documentation. Data processing and data analysis techniques go through three stages, namely data reduction, data presentation, and conclusion. The results of the research show that the mentoring program at SDIT Al Qalam Makassar firstly builds students' awareness of the importance of having an Islamic personality and a da'wah personality, secondly develops students' ability to strengthen their Islamic personality and preaching personality, thirdly grows students' appreciation and respect for the holy book Al-Qur'an, hadith, fatwas, and the works of ulama, Fourth, foster students' understanding of themselves, their families, Muslims, and the entity of the Indonesian nation from an Islamic perspective. Fifth, foster awareness in students as part of the Indonesian nation who have a sense of pride and love for their homeland. , empathize, and behave tolerantly which can be implemented in various areas of social and national life. Evaluation of input shows that several parts of the mentoring plan require improvements in mentor recruitment, facilities, and infrastructure. The process evaluation shows that the mentoring program was implemented well, namely that all series of mentoring activities were running but needed improvement during the implementation of the mentoring. Finally, product evaluation shows that holding.